Farmer-herder relations and conflict management in agro-pastoral zone of Niger - Turner, M.D.; Ayantunde, Augustine A.; Patterson, E.D.; Patterson, K.P. (2006)
Farmer-herder conflicts are enduring features of social life in the Sudano-Sahelian zone. A survey was carried out between August and December 2004 in four sites in Niger, namely Bokki, Katanga, Sabon Gida and Tountoubé to determine the proximate and long-term causes of conflict over natural resource use, to evaluate the appropriateness of existing institutional arrangements for managing conflicts and identify innovative options and incentives to reduce the incidence and severity of conflicts. The research was implemented in three phases: (1) collection of village and household level socioeconomic information, (2) social network mapping, and (3) collection of conflict history and conflict management strategies. Additionally, governmental and NGO agencies in Niamey that address conflict management and/or resolution at the regional and national levels were interviewed. The research employed both quantitative and qualitative survey instruments. Surveys collected information on: historical micro-geographies of cropping and herding in the area encompassing village territory; local day-to-day relationships between transhumance herders, settled herders, and farming households at the study site; nodes of communication under different types of disagreements and negotiative settings; documentation of past conflicts and role of government officials, customary authorities and NGOs in conflict management. Results from this study showed that in all sites, damage to crops was the first reported cause of conflict between farmers and herders. Crop damage is not limited to damage to growing crops on the field but also included unauthorized grazing of crop residues after harvest. Other causes of conflict reported were access to watering points, expansion of crop fields across corridors for animal passage and thefts of animal. The ability of rural communities to prevent and manage conflict is largely based on the strength of networks of communication between herding and farming interests, respected community leaders, and leaders in neighboring communities. Overall, the local institutional arrangements are functional and a high percentage of conflicts are effectively managed at local levels. In all the study sites except Bokki, there was a high level of involvement of internal mediators.